2021
DOI: 10.1371/journal.pone.0260671
|View full text |Cite
|
Sign up to set email alerts
|

Association between salt intake and long-term mortality in hemodialysis patients: A retrospective cohort study

Abstract: Background The association between salt intake and clinical outcomes in hemodialysis patients has been controversial. This study aimed to clarify the association between salt intake and mortality in hemodialysis patients. Method The present study included patients who underwent hemodialysis from June 1st 2016 to May 31st 2020. Corrected salt intake by ideal body weight was the main predictor of outcomes. Ideal body weight was calculated assuming that the ideal body mass index is 22 kg/m2 for the Japanese pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(42 reference statements)
0
2
1
Order By: Relevance
“…Nutritional guidance for haemodialysis patients in Japan is usually given to the patients regardless of who cooks in the home. While the salt intake standard for haemodialysis patients is less than 6 g/day, 14 the actual salt intake was 9.5 g in a previous study 32 and 9.96 g in our study, exceeding this standard. Although salt and fluid management based on an appropriate diet is vital to prevent the development of heart failure, the leading cause of death in haemodialysis patients, compliance with such management is low.…”
Section: Discussioncontrasting
confidence: 71%
“…Nutritional guidance for haemodialysis patients in Japan is usually given to the patients regardless of who cooks in the home. While the salt intake standard for haemodialysis patients is less than 6 g/day, 14 the actual salt intake was 9.5 g in a previous study 32 and 9.96 g in our study, exceeding this standard. Although salt and fluid management based on an appropriate diet is vital to prevent the development of heart failure, the leading cause of death in haemodialysis patients, compliance with such management is low.…”
Section: Discussioncontrasting
confidence: 71%
“…The same study reported that patients with high average salt intake are more likely to be younger, male, overweight, and with more nutrient intake paralleling sodium intake [138]. Similar findings were also demonstrated in Japanese hemodialysis patients [139,140]. As sodium accumulation varies by individual, the ideal level of sodium intake in both normal populations and patients with renal failure remains controversial.…”
Section: Salt-induced Inflammation In the Peritoneum During Renal Fai...mentioning
confidence: 64%
“…Unfortunately, it is known that efforts to intensify Na restriction may increase the risk of compromising energy intake [38]. A retrospective cohort study demonstrated that low-salt intake was related to high all-cause mortality in HD patients, possibly due to malnutrition in the context of excessive salt restriction [39]. Along the same line, another study reported that hyponatremia was associated with malnutrition, inflammation, and fluid overload [30], while a review of recommended dietary regimens in patients under HD showed that, since Na is used in a wide variety of foods, Na restriction could increase the risk of malnutrition and energy-protein loss.…”
Section: Discussionmentioning
confidence: 99%